Economic Security and Organizational Culture: Theoretical Approaches and Categorical Relationship - Mamychev, Alexei Y.; Sulimova, Elena A.; Yakovenko, Nataliya V.; Savvidi, Sofiya M.; Molchan, Aleksey S.; Dianova, Veronika A. (International Review of Management and Marketing, 2016)
Ensuring sustainable growth of the enterprise, to achieve its objectives, meeting the interests of managers and members of the workforce and society in general, are not possible without the development and implementation of effective business strategy, which in the modern economy is largely determined by the presence of a reliable system of its economic security and an appropriate level of organizational culture. Economic security, based on the ability of staff to counter the development of negative risk situations, becomes an important factor for sustainable and efficient operation of domestic enterprises. Of particular relevance acquire economic security issues in connection with the cases of hostile takeovers (hostile takeover attempts) that have been made against several dozen enterprises of Krasnodar Region for 2008-2014. The phenomenon of organizational culture is defined by a set of the most important positions taken by the members of the enterprise and receiving expression in the now claimed values that define people Landmarks their behavior and actions. The development of organizational culture in modern conditions has a growing impact on the performance of the company, its market position and its economic security. Keywords: economic security, organizational culture, production efficiency JEL Classifications: D2; D61; O16